ANALYSIS OF SUSTAINABLE DEVELOPMENT OF THE CAUCASIAN MINERAL WATERS BY ESTIMATION ECO-RECREATION POTENTIAL - Tatyana Alexandrovna Shebzukhova; Andrey Vadimovich Baturov; Valentina Fedorovna Kshishnevskaya (Современная наука и инновации, 2022)
The work discusses about the methods of estimation of anthropogenic influence on recreation potential of region of the Caucasian Mineral Waters. Integral indicator of sustainable development can be calculated on the basis on the individual indicators of environmental, economic and social development.